Epistaxis: etiological profile and treatment outcome in a teaching hospital in South India - N. K., Basheer; C., Jaya; V. T., Sabir (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Epistaxis is the most common otorhinolaryngological emergency worldwide. Minor bleeding episodes occur more frequently in children and adolescents, whereas severe bleed requiring otolaryngologic intervention often occur in older individuals. Treatment options can be conservative or surgical, the selection of which should be made considering the parameters: efficiency, complications, and cost-benefit. Methods: This was a prospective study done in 131 patients with epistaxis, in the Department of ENT, Government Medical College, Trivandrum, with the aim to determine the etiology and the outcome of the conservative and surgical management. Results: The most common causes of epistaxis were trauma and hypertension. The age incidence increased after forty years and majority had unilateral, anterior nasal, mild-moderate bleed. 79% of the cases were managed by conservative measures as opposed to only 21% who required surgical intervention. Success rate of anterior nasal pack and cauterisation of bleeding point was nearly 84%. Conclusions: Majority of cases of epistaxis can be successfully managed by conservative measures and surgical intervention may not be necessary in most cases. Cauterization of bleeding point is the best conservative method which can be offered to the patient though anterior nasal packing still remains the most preferred method to control the bleed. The most common causes of epistaxis being trauma and hypertension, reducing road traffic accidents and lifestyle illness can reduce the incidence of nasal bleed.